Effect of Sn concentration on the structural, morphological and thermoelectric transport properties of zinc Stannates thin films. Issue 23 (1st December 2022) - Khan, N. Abbas; Alnuwaiser, Maha Abdallah; Javed, Muhammad Rizwan; Ikram, Salma; Ali, A.; Ali, M. Yasir; Amami, Mongi; Nawaz, M. Asif; Javaid, K.; Hussain, M. Sharafat; Mahmood, K.
Abstract: This study aimed to set suitable Tin dopant concentration in ZnO based thin films to get optimal structural, morphological and thermoelectric properties. The samples under investigation were prepared by thermal evaporation technique using stoichiometric ratios of Zn and Sn powders. X-ray diffractograms showed that all grown samples are fully c-axis oriented but increasing Sn concentration caused a blue shift in XRD peak position. Raman spectrum of ZTO nanoparticles has confirmed the perfect wurtzite structure having an intense E2 mode. It was further showed that with increasing crystallite size, the frequency of E2 (highest peak) phonon mode decreases whereas its line width increases. The Seebeck coefficient has maximum value (800 μV/K) for un-doped sample while the value of electrical conductivity (5.2 S/cm) has maximum value for sample having Sn concentration 4%. This behavior of thermoelectric properties can be understood by the fact that Sn doping concentration increases the free carrier concentration in the host crystal of ZnO which resulted in the reduction of Seebeck coefficient and enhancement of electrical conductivity. This argument was further highlighted by the SEM measurements.